Anti-sticking material for firing insulator, manufacturing method and using method

By using anti-blocking formulations containing industrial alumina, quartz powder, kaolin and sodium carboxymethylcellulose, the powder loss and cracking of anti-blocking layers during insulator firing is solved, and more efficient production and better quality products are achieved.

CN119673587APending Publication Date: 2025-03-21CHONGQING PIGEON ELECTRIC PORCELAIN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411967668.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the firing process of existing insulators, the anti-adhesive layer of the anti-adhesive material brush on the carrier is prone to powder loss and cracking, resulting in low processing efficiency for workers and poor product quality.

Method used

A release material formula including 30-50 parts of industrial alumina, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of sodium carboxymethylcellulose is used to improve adhesion and water retention by adding sodium carboxymethylcellulose to ensure that the release layer is not prone to cracking after firing.

Benefits of technology

It effectively solves the problems of powder loss and cracking of the anti-adhesive layer, extends the service life, reduces the number of times of brushing anti-adhesive materials, reduces labor intensity and cost, and improves the quality and qualification rate of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673587A_ABST
    Figure CN119673587A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insulator firing, and particularly discloses an anti-sticking material for insulator firing, which comprises 30-50 parts of industrial alumina, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose. The preparation method of the anti-sticking material for firing the insulator comprises the following steps: S1, preparing materials: taking corresponding parts of raw materials according to the components in the anti-sticking material for firing the insulator; and S2, mixing the ingredients, adding water, and grinding into the anti-sticking slurry. The invention also provides a use method of the anti-sticking material for firing the insulator. The use method comprises the following steps: step 1, adding water into the anti-sticking material for firing the insulator, and grinding into anti-sticking slurry; and 2, brushing the anti-sticking slurry on the surface of the bearing body. The scheme is used for solving the problems that in the prior art, an anti-sticking layer prepared by brushing an anti-sticking material on a bearing body is prone to powder falling and cracking after an insulator porcelain piece is sintered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulator sintering, and in particular to an anti-sticking material for insulator sintering, a preparation method and a use method. Background Art

[0002] In the production of insulators, the porcelain parts of the insulators are placed on a kiln cart, and the kiln cart is pushed into the kiln for firing at a temperature of about 1200°C. After firing, the fired products (that is, the fired porcelain parts) are prone to adhesion to the carrier (the kiln cart or a special bowl or shelf on the kiln cart for supporting the porcelain parts).

[0003] To solve the above problem, technicians have proposed a method of brushing anti-sticking slurry made of anti-sticking material on the carrier on which the porcelain pieces are placed to form an anti-sticking layer (the anti-sticking material is also called an isolation material, and the carrier is an object such as kiln tools, pads, etc. that support the fired products). The anti-sticking layer formed by the anti-sticking material can prevent or reduce the adhesion between the porcelain pieces and the carrier after firing. This method is mentioned in existing patents, such as a special adhesive for electric porcelain rod-shaped firing with patent publication number CN113880556A.

[0004] The anti-sticking material formula disclosed in the above patent contains high plasticity clay, calcined kaolin and industrial alumina. The prices of calcined kaolin and industrial alumina are relatively expensive, especially the amount of calcined kaolin accounts for about 50%. Whether the calcined kaolin is directly purchased from outside or the enterprise itself makes kaolin through calcination process, both methods make the cost of calcined kaolin expensive, which is not conducive to the cost reduction and efficiency improvement of the enterprise. In order to reduce the production cost of the enterprise, the inventor only uses industrial alumina and kaolin to configure the anti-sticking material. Although the obtained anti-sticking material can achieve the anti-sticking effect after the anti-sticking layer is formed with slurry, the anti-sticking material is brushed into the pad bowl as a carrier with anti-sticking slurry, but the anti-sticking layer on the surface of the pad bowl has the problem of powdering and cracking. After the powdering and cracking problems occur, the workers deal with it by brushing a layer of anti-sticking slurry on the anti-sticking layer that has powdered or cracked. However, after using it once, the powdering and cracking problems occur again, which greatly reduces the efficiency of the workers.

[0005] As for large-sized disc-shaped suspension insulators with high mechanical damage loads, due to their large size, heavy weight and high requirements, the heads are placed in an inverted position for force support during firing, and they are placed on an anti-sticking layer that is prone to cracking and powdering, which also makes it easier for this type of disc-shaped suspension insulator porcelain to be defective after firing. Summary of the invention

[0006] The present invention aims to provide an anti-sticking material for insulator firing, so as to solve the problem in the prior art that the anti-sticking layer made by brushing the anti-sticking material on the carrier is easy to fall off and crack after the insulator porcelain is fired.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme:

[0008] An anti-sticking material for insulator sintering comprises 30-50 parts of industrial alumina, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose.

[0009] The principle and advantage of this scheme are: the anti-sticking material of this scheme improves the adhesion of the anti-sticking material after it is ground into anti-sticking slurry with water by adding sodium carboxymethyl cellulose, and also improves the water retention of the anti-sticking slurry, and makes each component evenly suspended and not easy to settle after being mixed evenly; it is not easy to cause the problem of powder falling due to the difficulty of adhesion of some materials with low binding force such as kaolin, nor will it cause the problem of cracking and lack of powder due to excessive shrinkage of kaolin and high plasticity clay due to high viscosity; and the high adhesion and high water retention of the anti-sticking slurry, coupled with the uniform distribution of each component, ensure that the anti-sticking slurry is not easy to crack after firing. In addition, in addition to ensuring that there is no cracking and powder falling during the first use, it can also ensure that the problem will not occur after repeated use for 4 times, thus solving the problem in the prior art that the anti-sticking slurry needs to be brushed every two or once for the pad bowl. The present invention greatly reduces the number of times the anti-sticking slurry is brushed, which helps to reduce labor intensity and cost.

[0010] In addition, the addition of quartz powder and kaolin has greatly reduced the cost of the entire anti-sticking material. The cost of the anti-sticking material has been reduced from 4,400 yuan / ton under the previous combination of industrial alumina and kaolin to less than 3,000 yuan / ton, a cost reduction of more than 40%.

[0011] Preferably, as an improvement, the industrial alumina comprises 38-42 parts, quartz powder comprises 40-50 parts, and kaolin comprises 10-15 parts.

[0012] Preferably, as an improvement, the sodium carboxymethyl cellulose is industrial grade sodium carboxymethyl cellulose.

[0013] The present invention also provides a method for preparing an anti-sticking material for insulator sintering, comprising the following steps:

[0014] S1. Ingredients: Take corresponding portions of raw materials according to the components of the anti-sticking material for insulator sintering;

[0015] S2. Mix the ingredients and add water to grind into an anti-sticking slurry.

[0016] The present invention also provides a method for using an anti-sticking material for insulator sintering, comprising the following steps:

[0017] Step 1: Take the anti-sticking material for insulator sintering and add water to grind it into anti-sticking slurry;

[0018] Step 2: Brush the anti-sticking slurry on the surface of the carrier.

[0019] Beneficial effects: After the anti-sticking slurry of the present invention is brushed on the surface of the carrier, the anti-sticking slurry can adhere to the carrier well; after firing, the anti-sticking layer formed by the anti-sticking slurry is not prone to cracking, powder loss, powder shortage and other problems. After the anti-sticking layer is formed, the fired products (ceramic parts) are not easy to or will not touch or stick to the carrier, thereby avoiding the problems caused by the bonding between the two.

[0020] Preferably, as an improvement, the anti-sticking slurry brushed on the carrier forms an anti-sticking layer on the surface of the carrier after the fired product is fired.

[0021] Preferably, as an improvement, step three is also included: placing a buffer pad after the anti-sticking slurry of the bowl is shade-dried or an anti-sticking layer has been formed, the buffer pad comprising a buffer layer embedded with anti-sticking material, the buffer layer is elastic, and the buffer layer is made of refractory material.

[0022] Beneficial effect: In actual production, after the anti-sticking layer is formed on the carrier, it can effectively prevent the fired porcelain parts from sticking to the carrier. However, for the porcelain parts used for large-sized disc insulators, because the porcelain parts of the disc-shaped suspension insulators are in contact with the carrier with their heads facing down and their umbrellas facing up during firing, the entire support is subjected to force using the small-sized end of the porcelain parts. The larger the outer diameter of the insulator, the greater the pressure on the head of the porcelain part. There are certain fine irregularities on the surface of the carrier, and it is still difficult to ensure its flatness even after the anti-sticking layer is formed. On the basis of excessive pressure on the head of the porcelain part, the head of the porcelain part after firing is prone to uneven force due to the presence of fine irregularities. In addition, the air permeability of the pressure-bearing surface of the head after contact is not good, resulting in Large-sized disc-shaped suspension porcelain parts are prone to micro-cracks on the head after firing. Large-sized disc-shaped porcelain parts are often used in scenarios where high electrical insulation performance and mechanical destructive strength requirements are high on high-voltage transmission lines, such as disc-shaped suspension insulators that can withstand mechanical destructive loads of 420KN, 550KN, and 800KN (this type of disc-shaped suspension insulator with high mechanical destructive load requirements and large size weighs about 14kg, while general small-sized disc-shaped suspension insulators weigh about 5kg). The appearance of cracks will make the mechanical strength of the insulator unable to meet the requirements, and the electrical insulation performance will also fail to meet the requirements, greatly reducing the firing pass rate of large-sized disc-shaped porcelain parts.

[0023] This solution can ensure that the weight of the fired product is evenly transferred to the carrier through an elastic buffer layer, thereby ensuring that the porcelain parts of the disc-type suspension insulator are evenly stressed during the firing process, greatly reducing or even avoiding the generation of microcracks, and improving the quality and pass rate of the product.

[0024] The refractory material of the buffer layer improves the service life and usage demand of the buffer pad. The anti-sticking material attached to the buffer layer has excellent refractory properties, which helps to improve the refractory properties of the buffer pad. At the same time, the anti-sticking material is embedded in the buffer layer to increase the compressive strength of the buffer layer. Under the heavy pressure of large-size disc suspension insulators, the increase in compressive strength helps the buffer layer not to be easily flattened to the point where it cannot be restored, thereby increasing the service life of the buffer pad. On the other hand, the buffer pad with anti-sticking material can also reduce adhesion to the burned products, thereby further increasing the service life of the buffer pad.

[0025] In addition, when the buffer pad needs to be replaced, the anti-sticking material on the buffer pad makes it difficult for the buffer pad to adhere to the carrier, thereby facilitating the replacement of the buffer pad.

[0026] Preferably, as an improvement, the surface of the buffer layer is covered with a layer of quartz sand, and the porcelain pieces to be fired are placed on the quartz sand layer for subsequent firing in the kiln.

[0027] Beneficial effects: When this solution is adopted, the quartz sand arranged on the surface of the buffer layer has multiple effects:

[0028] First, quartz sand can prevent the fired products (such as the porcelain parts of insulators) from sticking to the buffer layer, playing an isolating role. It can also increase the service life of the buffer pad through the high fire resistance of quartz sand. In the test, the service life of the buffer pad without quartz sand is only half of that of the buffer pad covered with quartz sand.

[0029] Secondly, the quartz sand not only makes the buffer pad play a cushioning role for the fired product, but also utilizes the gaps between the sands to form a porous structure, which helps to improve the quality of the contact parts of the fired product, making the difference between the contact parts and other parts when heated smaller.

[0030] Third, the anti-sticking material is attached to the buffer layer by first mixing the dry anti-sticking material with water and ball-milling it to form an anti-sticking slurry, and then allowing the anti-sticking slurry to soak the entire buffer layer. When the buffer layer is basically dry (that is, no water can be squeezed out of the buffer layer, and the anti-sticking material is embedded in various positions of the buffer layer), quartz sand is spread on the surface of the buffer layer. At this time, because the buffer layer just cannot squeeze out water, it is inevitable that moisture will still remain on the buffer layer. After the buffer layer contacts the fired product, the moisture will be absorbed by the fired product, and the presence of quartz sand will separate the moisture in the buffer layer from the fired product, thereby preventing the fired product from directly absorbing the moisture of the buffer pad and affecting the quality after firing.

[0031] Preferably, as an improvement, the particle size of the quartz sand is controlled within a range of 60 meshes to 180 meshes.

[0032] Preferably, as an improvement, the thickness of the quartz sand on the buffer layer is 1-2 mm; if the thickness of the quartz sand is thicker, it is easy for the fan to blow the excessively thick quartz sand onto the surface of the fired product during firing in the kiln (to ensure uniform temperature), thereby affecting product quality; and if the quartz sand is too thin, it is difficult for the quartz sand to cover the entire upper surface of the refractory wool.

[0033] Preferably, as an improvement, the buffer layer is fire-resistant wool.

[0034] Preferably, as an improvement, the refractory wool is immersed in the prepared anti-sticking slurry to achieve the embedding of the anti-sticking material in the refractory wool. Beneficial effects: The refractory wool has a refractoriness greater than 1400°C and has good elasticity, slurry absorption capacity and heat insulation effect. It can not only meet the requirements of the buffer function, but also be used in the high temperature environment of the kiln. It also has good slurry absorption capacity to absorb the anti-sticking material. In addition, it is simple to purchase and easy to make.

[0035] Preferably, as an improvement, the thickness of the buffer pad in the pad bowl is not less than 5 mm and not more than one half of the depth of the pad bowl, to ensure that the buffer pad can play a role while preventing the insulator from falling out of the pad bowl when the insulator tips over due to the buffer pad being too thick.

[0036] Preferably, as an improvement, the mass proportions of the quartz sand, refractory wool and anti-sticking material in the dry state are 10-20% of quartz sand, 40-60% of refractory wool and 25-45% of anti-sticking material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a front view schematic diagram of a method for using an anti-sticking material for insulator firing according to a first embodiment of the present invention (the disc-shaped suspension insulator is half-sectioned).

[0038] Figure 2 This is a three-dimensional schematic diagram of the first embodiment of the present invention before and after the anti-sticking layer is formed on the bowl.

[0039] Figure 3 It is a front view schematic diagram of the method of using the anti-sticking material for insulator sintering according to the second embodiment of the present invention.

[0040] Figure 4 It is a main cross-sectional schematic diagram of a buffer pad in a method for using an anti-sticking material for insulator sintering according to a second embodiment of the present invention. DETAILED DESCRIPTION

[0041] The following is further described in detail through specific implementation methods:

[0042] The reference numerals in the drawings of the specification include: a bowl 10 , an anti-sticking layer 11 , a buffer layer 20 , quartz sand 30 , and a porcelain piece 100 .

[0043] Embodiment 1

[0044] An anti-sticking material for insulator sintering comprises 30-50 parts of industrial alumina powder, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of industrial sodium carboxymethyl cellulose.

[0045] Industrial alumina powder contains up to 99.5% aluminum oxide.

[0046] The silicon dioxide content in quartz powder is greater than 98%. Quartz powder adopts natural ultra-fine powder material, and its particles ≥0.063mm are only about 3%.

[0047] Kaolin contains about 44% silicon dioxide and about 37.5% aluminum oxide, as well as a small amount of calcium oxide, magnesium oxide, potassium oxide and sodium oxide. It is a clay with a low hydration rate, with an average hydration rate of about 50%. It is also a clay with high plasticity, with an average bonding force of about 20.MPa. Specifically, the kaolin with the chemical composition shown in Table 1 below can be used:

[0048] Table 1 Chemical composition of kaolin

[0049] <![CDATA[SiO2]]> <![CDATA[AI2O3]]> <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> LL % % % % % % % % % 44.0 37.5 0.5 / 0.6 0.4 0.21 0.02 15.0

[0050] The anti-sticking material of this embodiment has low cost and is not prone to cracking, powder loss, powder shortage and other problems during firing and use.

[0051] Sodium carboxymethyl cellulose is industrial grade sodium carboxymethyl cellulose, which is in the form of fine powder and easy to agglomerate.

[0052] In a more preferred embodiment, the dry ingredients of the anti-sticking material include 38-42 parts of industrial alumina powder, 40-50 parts of quartz powder, 10-15 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose.

[0053] The inventors conducted the following multiple formulation tests during the research and development process. The test formulations and test results are shown in Tables 2 and 3 below, respectively:

[0054] Table 2 Different anti-sticking material formulas

[0055] project Industrial alumina (%) Quartz powder(%) Kaolin(%) Sodium carboxymethyl cellulose (%) Cost (Yuan) Recipe 1 88 0 12 0 4457 Recipe 2 60 28 12 0 3291 Recipe 3 10 78 12 0 1208 Recipe 4 20 68 12 0 1625 Recipe 5 50 31.5 18.3 0.2 2891 Recipe 6 40 45 13.8 1.2 2568 Recipe 6.1 38 47 13 2 2558 Recipe 6.2 42 43 14.5 0.5 2586 Recipe 6.3 39 46 13.5 1.5 2554

[0056] Note: The raw material prices in the above formula are calculated on a per ton basis. The highest price of sodium carboxymethyl cellulose is about RMB 10,000 / ton, industrial alumina is about RMB 5,000 / ton, and the prices of quartz powder and kaolin are both within RMB 1,000 / ton.

[0057] The effect of the anti-sticking material needs to be made into a slurry and then brushed on the pad bowl of the seat carrier for verification. For this purpose, this embodiment also provides a method for preparing the anti-sticking material for insulator firing, comprising the following steps:

[0058] S1. Ingredients: Take the corresponding number of raw materials according to the components of the anti-sticking material for insulator sintering;

[0059] S2. Mix the ingredients, ball-mill and sieve. The ball-milling process adopts one-time feeding, wherein the material: ball: water = 1:2:1.2, the ball-milling fineness is controlled to be 250 mesh (≥0.063mm), the sieve residue is 2-10%, and the anti-sticking slurry is formed after ball-milling. The water content of the anti-sticking slurry is 50%±5%.

[0060] Combination Figure 1 and Figure 2 This embodiment also provides a method for using an anti-sticking material for insulator sintering, comprising the following steps:

[0061] Step 1: Take the anti-sticking slurry prepared in the above manner;

[0062] Step 2: Brush the anti-sticking slurry on the inner surface of the bowl as the carrier. The thickness of the anti-sticking slurry brush needs to ensure that the anti-sticking layer formed by the anti-sticking slurry after firing in the kiln is 0.5mm thick. The bowl is made of porcelain material that can withstand the high temperature of the kiln. In the specific embodiment, the bowl is made of C130 porcelain.

[0063] Step 3: After the anti-sticking slurry is dried in the shade on the surface of the bowl to form an anti-sticking layer, place the product to be fired on the anti-sticking layer (to the extent that Figure 1 As shown in the figure), the fired porcelain part in this embodiment is a porcelain part of a disc-shaped suspension insulator.

[0064] The test results include cracking rate, powder loss rate and service life. If the anti-sticking layer of the mat bowl does not crack or powder after the first kiln firing, the mat bowl with the anti-sticking layer is put into the kiln again to simulate the firing of electric porcelain. The test is terminated when the anti-sticking layer on the mat bowl cracks or powders. The cracking rate and powder loss rate are the proportion of cracks or powder loss that occur after the first kiln firing after the anti-sticking slurry is brushed on the inner surface of the mat bowl. The service life of the mat bowl is defined as: the number of kiln firings from the first time the anti-sticking layer is formed on the mat bowl and fired in the kiln to the first time the anti-sticking layer powders or cracks. The test results of each formula are as follows:

[0065] Table 3 Test results of various anti-sticking material formulas

[0066]

[0067] From the above formula 1, it can be seen that the formula 1 is designed to solve the price of the anti-sticking material currently formulated with calcined kaolin, high plasticity clay and industrial alumina. Although the price is lower than the traditional method, the cost reduction is not too much, but the effect is very poor. After the introduction of quartz powder, the particle grading and adhesion of formula 2 are better than those of formula 1, and the cracking rate and powder loss rate are significantly improved under the physical and chemical action between the raw materials, especially the cracking rate is reduced by 10%, indicating that the addition of quartz powder helps to improve the formula, but the effect still needs to be improved.

[0068] After trying formula 3 and increasing the amount of quartz powder, the sieve residue was reduced to 1%. This is because quartz powder is very fine, with a particle size of 220-600 mesh, and can be directly sieved. However, the effect is worse in terms of cracking rate compared to formula 1, which shows that quartz powder should not be added too much.

[0069] Compared with Formula 1, Formula 4 has more advantages in terms of cracking rate and powder loss rate. The most prominent advantage is that the cost is reduced to more than 1,000 yuan / ton, which is equivalent to a significant reduction in cost while achieving basically the same or even slightly better results as the expensive Formula 1. However, this is far from enough for the firing of porcelain for large-sized disc suspension insulators with high mechanical load requirements.

[0070] Under Formula 5, after readjusting the dosage of industrial alumina, quartz powder, and kaolin, and adding 0.2% sodium carboxymethyl cellulose, the cracking rate was greatly controlled, and the cracking rate was reduced from 70-80% in Formulas 1-4 to 12%, and the powder loss rate was also reduced a lot. The cost was also reduced from more than 4,000 / ton in Formula 1 to more than 2,000 / ton, and the service life of the anti-sticking layer formed by the anti-sticking slurry brushed on the bowl was also extended from the original 1 time to 2 times.

[0071] Based on the great progress of Formula 5, a small adjustment was made to obtain Formula 6. From the test results of Formula 6, it can be seen that after increasing the amount of sodium carboxymethyl cellulose and quartz powder on the basis of Formula 5 and reducing the amount of industrial alumina and kaolin, the cracking rate and powder loss rate were further reduced to 1%. The cost is also more than 2,000 yuan / ton.

[0072] It can be seen that sodium carboxymethyl cellulose plays a very critical role in the anti-sticking material. Through analysis, it is found that the anti-sticking slurry with sodium carboxymethyl cellulose added has a slower evaporation rate of water, which means that the water retention is improved and the cracking problem caused by excessive shrinkage after subsequent firing is reduced; at the same time, the adhesion between the anti-sticking material and the bowl is also improved. From the test, it can be seen that the powder loss rate at the transition point between the inner wall of the bowl and the arc at the top of the inner cavity, where powder loss is prone to occur, is greatly reduced, which shows that its bonding with the bowl is also improved. In addition, the viscosity of sodium carboxymethyl cellulose allows the various components of the anti-sticking slurry that is evenly milled to be evenly suspended, which helps to improve the quality of the anti-sticking layer and the thickness uniformity of the anti-sticking layer.

[0073] In addition, the inventors also tested the addition of more sodium carboxymethyl cellulose to the anti-sticking material. For example, on the basis of Formula 6, 0.5% and 1% of sodium carboxymethyl cellulose were added to form an anti-sticking slurry. It was found that the anti-sticking slurry can still ensure a very low cracking rate and powder loss rate, and the service life can reach 4 times. The only inappropriate thing is that the anti-sticking slurry is more viscous, and it is more difficult for workers to brush the anti-sticking slurry, which affects efficiency.

[0074] In addition, in order to ensure process stability, Formula 6 was fine-tuned to obtain Formula 6.1, Formula 6.2 and Formula 6.3. The fine-tuned formulas can still meet extremely low cracking rate and powder loss rate, and the service life can reach 4 times. Compared with the situation where the bowl needs to be brushed with anti-sticking slurry every time it is fired twice or once in the kiln, the present invention greatly reduces the number of times the anti-sticking slurry is brushed, which helps to reduce labor intensity and cost.

[0075] In summary, the anti-sticking material of this embodiment not only has superior performance, but also significantly reduces the cost of raw materials, and its preparation method is simple and convenient. In addition, the anti-sticking material has a wide range of applications, and is suitable for forming an anti-sticking layer in the inner cavity of a bowl, and can also be used to embed an anti-sticking material in a cushion pad, showing excellent versatility and practicality.

[0076] Embodiment 2

[0077] Combination Figure 3 and Figure 4 This embodiment provides a method for using an anti-sticking material for insulator sintering, comprising the following steps:

[0078] Step 1: Mix the raw material components described in Example 1: industrial alumina powder, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of industrial sodium carboxymethyl cellulose. After the raw materials are evenly mixed, they are ball-milled and sieved to obtain an anti-sticking slurry. The ball milling process adopts one-time feeding, wherein the material: ball: water = 1:2:1.2, the ball milling fineness is controlled to 250 mesh (≥0.063mm), the sieve residue is 2-10%, and the anti-sticking slurry formed after ball milling has a moisture content of 50%±5%.

[0079] Step 2: brush the anti-sticking slurry on the surface of the carrier. In this embodiment, the carrier is a bowl, and the bowl is made of C130 porcelain;

[0080] Step 3: After the anti-sticking slurry is naturally dried on the carrier to form an anti-sticking layer, a buffer pad is placed on the anti-sticking layer, and then the porcelain piece to be fired is placed on the buffer pad. In this embodiment, the porcelain piece to be fired is a porcelain piece of a disc-shaped suspension insulator; the thickness of the anti-sticking layer in the inner cavity of the cushion bowl is 0.5mm-2mm. The thickness of the buffer pad in the cushion bowl is not less than 5mm and not more than half of the depth of the cushion bowl.

[0081] Step 4: Place the carrier with the porcelain pieces into the kiln for firing

[0082] The buffer pad in step 3 includes an elastic buffer layer, specifically, the buffer layer uses fluffy refractory cotton, the buffer layer is embedded with anti-sticking material, and a layer of quartz sand is laid on the upper surface of the buffer layer. The quartz sand is on the buffer layer so that after the product to be fired is placed on the buffer pad, the product to be fired will not directly contact the buffer layer. The particle size of the quartz sand is controlled to be 60 mesh-180 mesh, the thickness of the quartz sand layer is 1-2 mm, and the silicon dioxide content in the quartz sand is higher than 98%.

[0083] The anti-sticking material embedded in the buffer layer can be the buffer layer that is first soaked in the anti-sticking slurry, or it can be a structure in which the anti-sticking material in the anti-sticking slurry is distributed on the buffer layer after being fired in the kiln. The buffer layer is soaked in the anti-sticking slurry. After the anti-sticking slurry is fired, the anti-sticking material and the refractory wool form a whole to improve the fire resistance and compressive strength of the buffer layer.

[0084] This embodiment also provides a method for making a buffer pad: first take refractory cotton, soak the refractory cotton with the anti-sticking slurry formed by ball milling the anti-sticking material, and absorb the anti-sticking slurry under the water absorption of the refractory cotton. After the refractory cotton with the anti-sticking slurry is basically dry, sprinkle a layer of quartz sand particles on the surface of the buffer layer so that the quartz sand particles cover the surface of the refractory cotton. The thickness of the quartz sand needs to ensure that the fired porcelain parts will not directly contact the refractory cotton during subsequent use. The anti-sticking slurry used in the buffer pad is the same as the anti-sticking slurry used on the pad bowl.

[0085] The mass proportion of quartz sand, refractory wool and anti-sticking material in the dry state is 10-20% of quartz sand, 40-60% of refractory wool and 25-45% of anti-sticking material. The embodiment of the present invention ensures that the weight of the fired product is evenly transferred to the carrier through the elastic buffer layer even if the surface of the carrier is uneven, thereby ensuring that the porcelain parts of the disc-type suspension insulator are evenly stressed during the firing process, greatly reducing or even avoiding the generation of microcracks, and improving the quality and qualified rate of the product.

[0086] In addition, the quartz sand carried by the buffer pad of the present invention can prevent the fired disc-shaped suspended porcelain from contacting the buffer layer, thereby playing an isolating role and preventing the buffer layer from being torn and scrapped when the porcelain is removed due to adhesion to the porcelain, thereby greatly extending the service life of the buffer pad; in addition, the quartz sand not only enables the buffer pad to buffer the fired products, but also utilizes the gaps between the sand to form a porous structure to help improve the quality of the contact parts of the fired products, so that the difference between the contact parts and other parts when heated is smaller, which helps to improve the quality of the finished products of the fired porcelain.

[0087] In addition, because the buffer pad needs to be soaked in anti-sticking material when used for the first time, the anti-sticking material on the buffer pad still contains a certain amount of moisture before the buffer pad is put into the kiln for firing with the porcelain pieces for the first time. Porcelain pieces are highly absorbent. The presence of quartz sand isolates the anti-sticking material on the buffer pad from the porcelain pieces, ensuring that the firing quality of the porcelain pieces is not affected by the anti-sticking material.

[0088] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. An anti-sticking material for insulator sintering, characterized in that: The invention comprises 30-50 parts of industrial alumina, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose.

2. The anti-sticking material for insulator sintering according to claim 1, characterized in that: The industrial alumina comprises 38-42 parts, quartz powder comprises 40-50 parts, and kaolin comprises 10-15 parts.

3. A method for producing an anti-sticking material for insulator firing, characterized in that: The steps include: S1. Ingredients: raw materials of corresponding numbers of components in the anti-sticking material for insulator sintering according to any one of claims 1 to 2; S2. Mix the ingredients and add water to grind into an anti-sticking slurry.

4. A method for using an anti-sticking material for insulator firing, characterized in that: The steps include: Step 1: Take the anti-sticking material for insulator firing according to any one of claims 1 to 2, add water and grind into an anti-sticking slurry; Step 2: Brush the anti-sticking slurry on the surface of the carrier.

5. The method for using the anti-sticking material for insulator sintering according to claim 4, characterized in that: The anti-sticking slurry brushed on the carrier forms an anti-sticking layer on the surface of the carrier after the fired product is fired.

6. The method for using the anti-sticking material for insulator sintering according to claim 4, characterized in that: The method also includes step three: placing a buffer pad after the anti-sticking slurry of the bowl is dried in the shade or after the anti-sticking layer has been formed, wherein the buffer pad includes a buffer layer embedded with the anti-sticking material, the buffer layer is elastic, and the buffer layer is made of refractory material.

7. The method for using the anti-sticking material for insulator firing according to claim 6, characterized in that: The surface of the buffer layer is covered with a layer of quartz sand, and the porcelain pieces to be fired are placed on the quartz sand layer for subsequent firing in the kiln.

8. The method for using the anti-sticking material for insulator firing according to claim 7, characterized in that: The buffer layer is refractory wool, and the refractory wool is immersed in the prepared anti-sticking slurry to achieve embedding of the anti-sticking material in the refractory wool.

9. The method for using the anti-sticking material for insulator sintering according to claim 8, characterized in that: The thickness of the buffer pad in the pad bowl is not less than 5 mm and not more than half of the depth of the pad bowl.

10. The method for using the anti-sticking material for insulator sintering according to claim 8, characterized in that: The mass proportions of the quartz sand, refractory wool and anti-sticking material in the dry state are 10-20% of quartz sand, 40-60% of refractory wool and 25-45% of anti-sticking material.

Citation Information

Patent Citations

  • Special rod-shaped adhesive for loading and sintering of electrical porcelain

    CN113880556A